Safety Culture at Primary Healthcare Level: A Cross-Sectional Study among Employees with a Leadership Role - Klemenc-Ketiš Zalika; Poplas Susič Antonija (Sciendo, 2019)
An effective leadership is critical to the development of a safety culture within an organization. With this study, the authors wanted to assess the self-perceived level of safety culture among the employees with a leadership function in the Ljubljana Community Health Centre.